1997
DOI: 10.1111/j.1540-8159.1997.tb04841.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillators in Patients with Chagas' Disease: Are They Different from Patients with Coronary Disease?

Abstract: Chagas' disease is a parasitic affliction, endemic to certain regions of South America, which may lead to a chronic dilated nonischemic cardiomyopathy. Ten Chagasic patients were compared to 18 coronary patients undergoing transvenous ICD implantation for ventricular tachycardia (VT), ventricular fibrillation (VF), or aborted cardiac arrest. Indications for ICD implantation were either drug intolerance or refractoriness, or no inducible tachyarrhythmia at EPS. There were no statistically significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…Amiodarone appears to be effective in treating ventricular tachyarrhythmias, and death occurs as a result of either refractory HF or arrhythmias (485). Device therapy including the ICD is frequently used in the late phase (486). In those with good functional status (e.g., NYHA functional class I and II), SCD is a rare event when patients are treated with amiodarone.…”
Section: Myocarditismentioning
confidence: 99%
“…Amiodarone appears to be effective in treating ventricular tachyarrhythmias, and death occurs as a result of either refractory HF or arrhythmias (485). Device therapy including the ICD is frequently used in the late phase (486). In those with good functional status (e.g., NYHA functional class I and II), SCD is a rare event when patients are treated with amiodarone.…”
Section: Myocarditismentioning
confidence: 99%
“…Pre-and intraoperative electrophysiological mapping has allowed the identification of the site of origin and its relationship to akinesia and dyskinesia areas usually located in the left ventricle 227 . The analysis of biopsy specimens obtained during surgical treatment guided by electrophysiological mapping has confirmed the presence of the scar substrate 228 , showing that the inferior, lateral and basal LV walls were the most frequent sites of origin of SVT, independently of the presence of apical aneurysm 225 . With technological development, the surgical treatment of SVT in CCC has been gradually replaced by the treatment via catheter, being currently rarely recommended, except for highly selected patients (Table 9).…”
Section: Surgical Ablationmentioning
confidence: 99%
“…In addition, SVT can have multiple sites of origin, making the task of eliminating all circuits a challenge 201,207,213,229,230 . In general, the site of origin of well-tolerated recurring SVT can be identified and the SVT interrupted in 60%-80% of the patients, but rapid and poorly tolerated SVT are frequently induced in the final assessment of the procedure 201,213,[227][228][229] . During long-term follow-up, at least 50% of the patients undergoing conventional ablation have clinical relapse, justifying the maintenance of antiarrhythmic drugs or ICD implantation 230 .…”
Section: Catheter Ablation Of Svt In CCCmentioning
confidence: 99%
“…All of these studies investigated patients for whom ICD was indicated for the prevention of arrhythmias secondary to ChD. Studies by Muratore et al (50), (51) and Fonseca et al (53) found no difference between the populations with and without Chagas disease in the numbers of arrhythmia episodes, shocks, and deaths. In contrast, the studies by Martinelli-Filho et al (44) , Rabinovich et al (51) , Moreira (49) , Cardinalli-Neto et al (54) , Cardinalli-Neto et al (55) , Barbosa et al (52) and the ICD registry for patients with Chagas disease in Latin America, published in 2009 (56) , found differences between the chagasic and non-chagasic populations.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 99%
“…Studies of ICD implantation in patients with ChD have aimed to evaluate its effi cacy and safety and to identify predictors of appropriate therapy (47), (48) . In addition, several studies have compared the results of ICD implantation in ChD patients with the results of ICD implantation in the non-chagasic population to identify similarities and differences between these populations (44), (49)(50)(51)(52) . All of these studies investigated patients for whom ICD was indicated for the prevention of arrhythmias secondary to ChD.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 99%